Product Quality, Brand Image and Brand Trust Towards Customer Satisfaction of Telkomsel SIM Card Users in Lubuklinggau City - Nurlael, Sarifa; Aprianto, Ronal; Rabeta, Yulpa; Suwarno, Suwarno; Kesuma, Indrawati Mara (CV. Rayyan Dwi Bharata, 2022)
This study aims to determine the influence of product quality, brand image and brand trust on customer satisfaction of Telkomsel SIM card users in Lubuklinggau city. In this study, data collection was carried out by distributing questionnaires to 80 respondents of Telkomsel customers in Lubuklinggau city using the incidental sampling method to find out respondents' responses to existing variables. The analysis was carried out using the Structural Equation Modeling (SEM) method based on partial least squares (PLS). The results of the analysis show that product quality has a positive and significant effect on telkomsel sim customer satisfaction, brand image has a positive and significant effect on telkomsel sim customer satisfaction. And the brand trust variable has a positive and significant effect on the satisfaction of TelkomseI SIM card handling.